2020
DOI: 10.1080/21870764.2020.1712798
|View full text |Cite
|
Sign up to set email alerts
|

Properties of foamed glass upon addition of nanocarbon and sintering temperatures

Abstract: As a blowing agent, 2-10 wt% of nanocarbon (NC) was added 10 µm glass powder (CaO, MgO, Al 2 O 3 , SO 3 , 83 wt%-SiO 2) and sintered at 700-900°C to fabricate foamed glasses with closed pores that were 62-2200 µm. Optical microscopy was used to examine the microstructure and pore size. Compressive strength tester and a heat flow meter were used to examine the changes in mechanical strength and thermal conductivity. The microstructure examination results showed that was performed at 700°C, 297.9-351.3 µm pores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The addition of polysiloxane leads to a smaller pore size because the growth of the pores is suppressed by the increased viscosity and bonding in the glass matrix during the heat treatment process of polysiloxane. The pores of the foam glass are produced by the carbon of the added nano-carbon during heat treatment in the following reaction: C + O 2 → CO 2 (g) ↑ [12]. However, as polysiloxane is added, the viscosity and bonding of the glass matrix increase, which discourages the volume expansion of the CO 2 gas and results in a decreased pore size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of polysiloxane leads to a smaller pore size because the growth of the pores is suppressed by the increased viscosity and bonding in the glass matrix during the heat treatment process of polysiloxane. The pores of the foam glass are produced by the carbon of the added nano-carbon during heat treatment in the following reaction: C + O 2 → CO 2 (g) ↑ [12]. However, as polysiloxane is added, the viscosity and bonding of the glass matrix increase, which discourages the volume expansion of the CO 2 gas and results in a decreased pore size.…”
Section: Methodsmentioning
confidence: 99%
“…Ma et al [11] employed CaCO 3 as the blowing agent and varied its amount, reporting an improved bending strength from 43.4 MPa to 109.6 MPa; however, the porosity was below 20 %, which led to a heavier weight. Kim et al [12] reported that they successfully obtained the 500 µm-closed pored foam glass with 6 wt% nano-carbon addition and at a low temperature of 750 °C due to the enhanced blowing reaction by the nano-carbon.…”
Section: Introductionmentioning
confidence: 99%
“…It is prepared with waste materials as the main source (e.g., waste glass, [1][2][3] fly ash, [4][5][6][7] and industrial slag 8,9 ) and some appropriate additives and foaming agents, and the foaming temperature is at ∼900 • C. The general foaming agents used are sodium carbonate, 10 eggshell, 11 calcium carbonate, 12 Mn 3 O 4 , and carbon. 13,14 At a designated temperature, foaming agents release gaseous species as a result of their thermal decomposition or due to the thermally activated reaction. Traditional foam glass has attracted significant interest due to its excellent mechanical properties (mechanical strength values of 5.61-23.73 MPa), 15 heat resistance [thermal conductivity of .0375-.066 and .260 W/(m K)], 16,17 and fire resistance (indirect exposure at temperatures between 400 and 600 • C for 3 h).…”
mentioning
confidence: 99%
“…It is prepared with waste materials as the main source (e.g., waste glass, 1–3 fly ash, 4–7 and industrial slag 8,9 ) and some appropriate additives and foaming agents, and the foaming temperature is at ∼900°C. The general foaming agents used are sodium carbonate, 10 eggshell, 11 calcium carbonate, 12 Mn 3 O 4 , and carbon 13,14 . At a designated temperature, foaming agents release gaseous species as a result of their thermal decomposition or due to the thermally activated reaction.…”
mentioning
confidence: 99%